1987
DOI: 10.1016/0005-2736(87)90035-6
|View full text |Cite
|
Sign up to set email alerts
|

Binding of phospholipids to the phosphatidylinositol transfer protein from bovine brain as studied by steady-state and time-resolved fluorescence spectroscopy

Abstract: The phosphatidylinositoi transfer protein isolated from brain, liver, heart and platelets was found to be present in two subforms which could be distinguished on the basis of the isoelectric points. In this study we have demonstrated that the two subforms isolated from bovine brain are due to the presence of either phosphatidylinositol or phosphatidylcholine in the lipid binding site of the protein. The transfer protein accommodates one phosphatidylinositol molecule in the binding site. The binding site for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…This difference in affinity is caused by the interaction of the protein with the polar headgroup, since the accomodation of the acyl chains of both PI and PC on the protein is very similar (Ref. 22 and Van Paridon et al, manuscript submitted). Modification of the inositol ring by periodate oxidation and subsequent reduction by sodium borohydride, or phopshorylation at the 4-position, greatly reduced the transport by PI transfer protein [18,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference in affinity is caused by the interaction of the protein with the polar headgroup, since the accomodation of the acyl chains of both PI and PC on the protein is very similar (Ref. 22 and Van Paridon et al, manuscript submitted). Modification of the inositol ring by periodate oxidation and subsequent reduction by sodium borohydride, or phopshorylation at the 4-position, greatly reduced the transport by PI transfer protein [18,32].…”
Section: Discussionmentioning
confidence: 99%
“…65% of the protein was found to contain an endogenous PI molecule [22]. From the PI to PC ratio of 0.11 in a bovine brain homogenate (34) and from the Kra value of 15.6, one can calculate that 63% of the PI-transfer protein should contain an endogenous PI molecule.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the voltage to 120 V showed that the dissociation between PG and PI-TPR, as apparent from the appearance The present measurements do not allow one to distinguish between these two residues, but do reveal that the noncovalent interaction between PG and PI-TPR in the gas phase is very strong and approaches that of a peptide bond. Since PI-TPR from mammalian cells carries either a PI or a PC molecule (5,27,28), we have analyzed these complexes as well. As shown in Figure 5, PI and PG dissociated from PI-TPR at a relatively high cv, whereas PC dissociated at a cv comparable to that observed for the PC/PC-TP complex.…”
Section: Esi-tof Analysis Of the Phosphatidylcholine Transfermentioning
confidence: 99%